Unity and differentiation of the duration of annual basic leave in Ukraine - Bortnyk, S. M. (Bulletin of Kharkiv National University of Internal Affairs, 2023)
The current legal regulation of the duration of annual basic leave has been studied. It has been noted that this is the longest period of rest for employees provided for by national labour legislation. It allows the employee to have a more complete approach to rest, restore working capacity, improve health, and also satisfy important needs and interests in education, sports, childbirth and upbringing. Every employee can exercise the right to annual basic leave every year. Annual basic leave is granted to all employees without exception, regardless of their place of work, the labor function they perform, the form of ownership of a legal entity, the term of an employment contract or contract, for a working year. Such a year is counted from the date of conclusion of the employment contract (contract) by the relevant employee. Scientists’ points of view on the content of the category “unity and differentiation in labour law” have been investigated. An author’s definition of the terms “unity of the duration of annual basic leave” and “differentiation of the duration of annual basic leave” has been provided. The unity of the duration of annual basic leave should be understood as the establishment of a single name for this leave in all acts of national legislation and the establishment of its duration common to all employees. The differentiation of the duration of annual basic leave means the establishment by law of a longer duration of annual basic leave than its total duration, depending on the employee’s age, disability, specifics of work at the enterprise, institution, organisation, working conditions and nature of work. The understanding of the essence of unity and differentiation of the duration of annual basic leave has been further developed. Some recommendations for improving the provisions of modern labour legislation in the area of annual basic leave regulation have been proposed. The expediency of bringing the terminology of special laws in compliance with the provisions of the Law of Ukraine “On Vacations”, in particular, with regard to the term “annual basic leave”, has been substantiated.